Annotating pathogenic non-coding variants in genic regions - Sahar Gelfman (Nature Portfolio, 2017)
While non-coding synonymous and intronic variants are often not under strong selective constraint, they can be pathogenic through affecting splicing or transcription. Here, the authors develop a score that uses sequence context alterations to predict pathogenicity of synonymous and non-coding genetic variants, and provide a web server of pre-computed scores.